Economic valuation of eco-tourism resources in Pulau Perhentian Marine Park, Malaysia - Akhter, Shammi (2014)
The Pulau Perhentian Marine Park (PPMP) is one of the most beautiful coral reefs islands in Malaysia. Therefore, tourism is developing rapidly at PPMP and contributes significantly to the economy. However, pollution and resource exploitation have been increased due to rapid tourism development. Though Marine Park is created to protect coral reefs and associated flora and fauna however, the rules are not applying strictly, resulting in resource damages. One of the main objectives is to assess the activities that caused damages to the environment and resources at PPMP and to suggest mitigating actions in order to prevent further deterioration. A damage schedule approach via the paired comparison method was used to assess the damaging activities at PPMP. A survey was conducted by a quota sample of 144 respondents consisting of both the resource dependent and the expert groups. This study also estimated the conservation value of marine environment and resources at PPMP using the contingent valuation method. Convenient samples of 250 tourists were interviewed to elicit their willing-to-pay (WTP) an increasing amount of entry fee for the conservation of the marine environment and resources in PPMP. This study used both the single and double-bounded contingent valuation methods to estimate the WTP. The results showed that improper sewage discharge by small resorts was the most damaging activities at PPMP, followed by direct disposal of sewage from village into sea (DS), and littering on the beach (LB) with a scale value of 65, 47.45 and 44.8, respectively. To mitigate the improper sewage discharge by the small resorts, all stakeholders suggested that imposing high damage payment, proper maintenance of septic tanks, and stopped all waste water channels passing straight to the sea would be the most effective steps. Direct disposal of sewage from village into the sea could be mitigated by introducing and practicing an environmental awareness programs to the villagers. Moreover, more regular collection of waste, installing composting systems for organic wastes could be able to mitigate this problem. Strict prohibition, improvement of information system, and more waste bins along the beaches could be effective steps to mitigate the problems of littering on the beach at PPMP. About 61.2% of the tourists were willing-to-pay an increased amount of entry fee to conserve marine environment and resources in PPMP. The median WTP per person per visit ranged from RM17.98 to RM21.72 that could contribute to an aggregated benefit from 1.62 million to 1.96 million in 2011. In addition, the foreign visitor’s median WTP per person per visit was much higher compared to locals, ranging between RM23.89 to RM27.86 and RM8.64 to RM13.40 respectively. Marine parks authority could apply different price system for both foreign and local tourists. This study would like to recommend RM23.18 for foreign tourists and RM8.64 for local tourists. Therefore, the above results of the study could be beneficial to the Marine Park authority in setting appropriate entrance fee at PPMP and taking adequate conservation activities to protect marine environment and resources to prevent them from deteriorating further.